2005
DOI: 10.1016/j.orthres.2005.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Activation of NF-κB signalling and TNFα-expression in THP-1 macrophages by TiAlV- and polyethylene-wear particles

Abstract: Wear particles are believed to induce periprosthetic inflammation which contributes to periprosthetic osteolysis. TNFalpha plays a pivotal role in the pathogenesis of this process. The molecular mechanisms leading to the development of periprosthetic inflammation with upregulated TNFalpha expression in monocytic cells in response to different wear particles have yet to be defined. In this study we evaluated the effects of polyethylene- and TiAlV-particles on activation of NF-kappaB signalling pathways and TNFa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…Our current studies using PMA stimulated THP-1 cells which were exposed to UHMWPE particles moderately increased TNF-α expression, and is consistent with a previous study with a similar dose (∼1 × 10 9 particles/ml) of polyethylene particles [36]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our current studies using PMA stimulated THP-1 cells which were exposed to UHMWPE particles moderately increased TNF-α expression, and is consistent with a previous study with a similar dose (∼1 × 10 9 particles/ml) of polyethylene particles [36]. …”
Section: Discussionsupporting
confidence: 91%
“…Previous studies using titanium wear particles and differentiated THP-1 cells have shown variable results [35, 36], which may be due to the type and dose of particles and cell differentiation strategy. Our current studies using PMA stimulated THP-1 cells which were exposed to UHMWPE particles moderately increased TNF-α expression, and is consistent with a previous study with a similar dose (∼1 × 10 9 particles/ml) of polyethylene particles [36].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, macrophages of the THP-1 cell line were exposed to particles of polyethylene- and titanium alloy, which resulted in significant activation of both NF-κB and TNF-α promoters and TNF-α release in a dose dependent manner. [83]. …”
Section: Nf-κb Signaling In Chronic Inflammationmentioning
confidence: 99%
“…However, we did investigate the inhibition of pro-inflammatory cytokines secretion in vitro. Secondly, UHMWPE is more important to today's joint replacement surgeons because significantly more polyethylene particles (70-90%) appear in tissues around metal-on-polyethylene prostheses [56,57]. However, though metal particles are relatively fewer in the tissue, they are also an important factor contributing to osteolysis [58][59][60].…”
Section: Cells That Had Beenmentioning
confidence: 99%